The Role of Al-Qur’an Educational Institution Al-Husna in Producing Huffadz in Sei Kepayang District Asahan Regency - Rika Kumala Sari; Ali Imran Sinaga; Salim Salim (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Memorizing the Qur'an is known as hafiz or huffaz (memorizers/maintainers of the Qur'an). Various Qur'anic educational institutions seek to create students who memorize the Qur'an, including TPQ Al-Husna in Sei Kepayang District, Asahan Regency. This article aims to describe and analyze the role of Al-Husna Al-Qur'an Education Institutional (TPQ) in producing huffaz in Sei Kepayang District, Asahan Regency. This article uses a qualitative approach with a descriptive analysis method. Data was collected using interview, observation, and document analysis techniques. Furthermore, the data were analyzed through data reduction (sorting) techniques, data presentation, and drawing conclusions. The results of this article indicate that TPQ Al-Husna plays a role in producing huffaz in Sei Kepayang District, Asahan Regency, this is evidenced by the recognition of huffaz who learn to read the Qur'an properly and correctly according to the rules of recitation, systematically memorize the Qur'an. a (30 juz), and motivate students to excel in the field of memorizing the Qur'an at the district, provincial and even national level musabaqah. Supporting this role, the organizers of TPQ Al-Husna also provide special dormitory facilities for fostered students and the recruitment of competent teachers for students.